Perbandingan Performansi Mini PC 1.2 GHz dan 1.5 GHz sebagai Server Layanan Video Call menggunakan Codec H264 - Hana Via Eka Amalia Hartono; Martono Dwi Atmadja; M. Abdullah Anshori (Jurnal Jaringan Telekomunikasi, 2020)
The problem that exists on the server for video call services is that the use of the server usually uses a PC that has FreePBX installed and requires some hardware that must be provided, such as a CPU with 312 MB of memory specifications used, 800 MHz Pentium III CPU. There is an alternative to building a server with better specifications than conventional CPUs in supporting video call services using a Mini PC. One type of popular Mini PC is the Raspberry Pi. Based on the results of a comparative study, two Mini PC servers are able to serve customer capacity at video resolution for the H264 codec. Two Mini PC servers are able to serve as many as 10 client video call communications with CPU and RAM usage on the Raspberry Pi 4 compared to the Raspberry Pi 3 with an average CPU usage of 39.8% and RAM Usage 282 MB viewed using the HTOP command on putty. Determination of the amount of user capacity is determined based on the number of clients communicating simultaneously, and the CPU and RAM usage on the Mini PC.